Analisis dan Perbaikan Usability Website Unit Aktivitas Band Universitas Brawijaya Menggunakan Focus Group Disccusion dan Extended Goal Question Metric Untuk Meningkatkan User Experience - Muhammad Rizqinovniari; Retno Indah Rokhmawati; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Band Activity Unit of Brawijaya University (UAB UB) has a website that is used for publication media and disseminates information about work programs and information about UAB UB. The use of the UAB UB website is also to disseminate information about events organized by UAB UB starting form the scale on campus and nationally. The importance of increasing user experience on the website is by analyzing existing problems and generating recommendations that are useful for maintaining old user and adding new users so that information can be spread. The purpose of this research is to analyze and redesign UX UAB UB website to improve UX using Focus Group Disccusion and Extended Goal Question Metric. Focus Group Disccusion is used to analyze the problems that exist on the UAB UB website with 12 participants for 2 hours, then the result are entered into Extended Goal Question Metric method to determine rhat goals to look for and raise recommendations for improvement. As a result of the study it was found the positive increace in difference in the old design to the highest new design is the â€œExcitingâ€ item.